2006
DOI: 10.1186/1471-2458-6-89
|View full text |Cite
|
Sign up to set email alerts
|

Identifying strategies to improve access to credible and relevant information for public health professionals: a qualitative study

Abstract: BackgroundMovement towards evidence-based practices in many fields suggests that public health (PH) challenges may be better addressed if credible information about health risks and effective PH practices is readily available. However, research has shown that many PH information needs are unmet. In addition to reviewing relevant literature, this study performed a comprehensive review of existing information resources and collected data from two representative PH groups, focusing on identifying current practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 17 publications
3
88
0
Order By: Relevance
“…Similar findings have been reported among public health decision-makers in Canada and the US. These studies have reported that public health professionals at all decision-making levels want quick and easy access to synthesized, high-quality evidence that clearly articulates implications for policy and practice [5,27,40]. Given these findings it is likely that health care decision-makers engaged in the provision of health care services to individuals, families, groups, and populations in a variety of community-based settings, experience similar information needs and preferences to the ones reported in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported among public health decision-makers in Canada and the US. These studies have reported that public health professionals at all decision-making levels want quick and easy access to synthesized, high-quality evidence that clearly articulates implications for policy and practice [5,27,40]. Given these findings it is likely that health care decision-makers engaged in the provision of health care services to individuals, families, groups, and populations in a variety of community-based settings, experience similar information needs and preferences to the ones reported in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…While the public health workforce is extremely diverse [55-60] and public health information sources are often disparate and unstandardized [46, 55, 56, 60], several themes held constant. Public health professionals need timely access to current data from reliable, high quality sources [9, 55, 58, 59, 61, 62]. Furthermore, public health professionals need synthesized and collated data on relevant information such as best practices, effective prevention strategies or interventions, and evidence-based research, to name a few [9, 55, 59, 61, 63].…”
Section: Resultsmentioning
confidence: 99%
“…Public health professionals need timely access to current data from reliable, high quality sources [9, 55, 58, 59, 61, 62]. Furthermore, public health professionals need synthesized and collated data on relevant information such as best practices, effective prevention strategies or interventions, and evidence-based research, to name a few [9, 55, 59, 61, 63]. Public health professionals gather information from colleagues, literature and health departments [55, 57, 58, 62, 64].…”
Section: Resultsmentioning
confidence: 99%
“…The epistemological/philosophical and methodological challenges in this field are considerable, and there is still some cynicism about the ability of systematic reviews to deliver meaningful messages (other than simply underlining the need for more research); but such reviews, performed thoughtfully, and with the input of users, help redress the undue emphasis still placed on single studies, and form a rational, and, to users, acceptable basis for evaluating complex social interventions, and for supporting public health decision making (LaPelle et al, 2006;Lavis et al, 2005, Dobbins et al, 2007.…”
Section: Discussionmentioning
confidence: 99%